ARRHYTHMIC SYNDROME IN CHILDREN AND ADOLESCENTS WITH MINOR CARDIAC ANOMALIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Diseases of the circulatory system occupy one of the leading places in the structure of cardiorheumatological pathology in children over the past decades. Studies devoted to the study of the prevalence of heart rhythm disorders in the child population allow not only to resolve controversial issues of norm and pathology, but also to establish age periods of risk of developing arrhythmia, concentrate efforts on the most significant pathological conditions and determine the direction of preventive programs. Analysis of the evolution of heart rhythm and conduction disorders over the past decade allows us to conclude not only about the increase in their frequency, but also about their rejuvenation, so in adolescents in the structure of functional diseases of the cardiovascular system, heart rhythm disorders make up 60.8%. Great importance in the pathophysiology of arrhythmias is currently attached to disorders of neurovegetative regulation of heart rhythm, electrolyte disturbances, and hereditary predisposition. However, the listed factors contribute to the formation of arrhythmias only in children with a special structure and electrophysiology of the cardiac conduction system. Many aspects associated with the mechanism of occurrence of individual clinical syndromes, in particular the occurrence of rhythm and conduction disturbances in children with MAC, their course and prognosis in specific patients, remain poorly studied, and the assumptions made on this account are controversial. Due to increased environmental loads and improved capabilities of modern diagnostics, the number of patients with connective tissue dysplasia syndrome (CTD) has increased sharply. The predominance of young people among them, and therefore of working age, conscription and childbearing age, gives this problem not only medical but also social significance. The issue of developmental anomalies of the cardiovascular system in hereditary connective tissue disorders (HCTD) attracts special attention of cardiologists, since such anomalies lead to the development of clinically significant pathological conditions and life-threatening, and sometimes fatal, complications.